Colorectal cancer with intestinal perforation – a retrospective analysis of treatment outcomes - Banaszkiewicz, Zbigniew; Woda, Łukasz; Tojek, Krzysztof; Jarmocik, Paweł; Jawień, Arkadiusz (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : Colorectal cancer (CRC) is one of the leading cause of death in European population. It progresses without any symptoms in the early stages or those clinical symptoms are very discrete. The aim of this study was a retrospective analysis of treatment outcomes in patients with colorectal cancer complicated with intestinal perforation. Material and methods : A retrospective analysis of patients urgently operated upon in our Division of General Surgery, because of large intestine perforation, from February 1993 to February 2013 has been made. Results were compared with a group of patients undergoing the elective surgery for colorectal cancer in the same time and Division. Results Intestinal perforation occurred more often in males (6.52% vs. 6.03%), patients with mucous component in histopathological examination (9.09% vs. 6.01%) and with clinicaly advanced CRC. Patients treated because of perforation had a five-fold higher 30 day mortality rate (9.09% vs. 1.83%), however long-term survival did not differ significantly in both groups. After resectional surgery in 874 patients an intestinal anastomosis was made. Anastomotic leakage was present in 23 (2.6%) patients. This complication occurred six-fold more frequently in a group of patients operated upon because of intestinal perforation (12.20% vs. 2.16%). Conclusions : In patients with CRC complicated with perforation of the colon in a 30-day observation significantly higher rate of complications and mortality was shown, whereas there was no difference in distant survival rates.